2013
DOI: 10.1038/cddis.2013.134
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-199a-5p protects hepatocytes from bile acid-induced sustained endoplasmic reticulum stress

Abstract: Sustained endoplasmic reticulum (ER) stress has been linked to cell death and the pathogenesis of many liver diseases, including toxic liver, cholestasis, and infectious liver disease. The cellular pathways that attenuate hepatic ER stress have been the focus of many recent studies, but the role of microRNAs (miRNA) in this process remains unknown. Here, we report that one of the most abundant miRNAs in hepatocytes, miR-199a-5p, was elevated in both bile acid- and thapsigargin (TG)-stimulated cultured hepatocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 37 publications
2
44
0
1
Order By: Relevance
“…In several cancer cell lines, GRP78 was reported to be regulated by miR-199a-5p as well as miR-30d and miR-181a and cooperatively suppressed GRP78-mediated chemoresistance (45). Similarly, Dai et al (5) reported that miR-199a-5p was evaluated during hepatic ER stress and directly regulated the expression of GRP78 in hepatocytes. Downregulation of miR-181b produced neuroprotection against ischemic injury via upregulating GRP78 (34).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In several cancer cell lines, GRP78 was reported to be regulated by miR-199a-5p as well as miR-30d and miR-181a and cooperatively suppressed GRP78-mediated chemoresistance (45). Similarly, Dai et al (5) reported that miR-199a-5p was evaluated during hepatic ER stress and directly regulated the expression of GRP78 in hepatocytes. Downregulation of miR-181b produced neuroprotection against ischemic injury via upregulating GRP78 (34).…”
Section: Discussionmentioning
confidence: 95%
“…Cells were exposed to rotenone (Sigma, St. Louis, MO) at various concentrations (1,5,10,20, and 50 M) (28) for the indicated times before being harvested for analysis. For miRNA transfection, cells were transfected with miR-384-5p mimics or inhibitors using Lipofectamine 2000 (Invitrogen) at a final concentration of 50 nM for 24 h prior to rotenone (20 M) exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, accumulating studies have highlighted the importance of cellular miRNAs in regulating HCV pathogenesis due to their versatility (Waldron and Holodniy, 2014). miR-199a-5p, a mature form of miR-199a, has been found to be effective in the inhibition of human hepatocellular carcinoma (Shen et al, 2010), in promoting liver repopulation (Mobus et al, 2014) and in hepatocyte protection (Dai et al, 2013), but little is known regarding its efficacy in HCV treatment. In the present study, we identified miR-199a-5p overexpression in HCV-infected cells and liver biopsy specimens, suggesting the potential function in the development of HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, when vitamin C was supplied to Huh-BAT cells, this bile acid-induced reactive oxygen species production and apoptotic cell death were significantly attenuated. We then explored the possible mechanism of apoptosis attenuation by vitamin C and found that the activations of caspase 12, 3, 9 and 7 by bile acid were significantly attenuated by vitamin C, which suggested that activation of apoptotic signaling is ameliorated by vitamin C. Several studies have demonstrated that sustained ER stress has been linked to cell death and the pathogenesis of cholestatic liver diseases (Dai et al, 2013). In addition, our previous report (Jang et al, 2014) and others (Pastorekova et al, 2008;Szegezdi et al, 2006) showed that bile acid induced apoptosis through ER stress-related JNK activation.…”
Section: Discussionmentioning
confidence: 99%